Comparing the Pulmonary-Spirometry In Laboratory Workers Who Wear Acchadana® and KN95® Masks - Fathur Nurkholis; Resti Ariani; Awal Prasetyo; Rina Puspita`; Udadi Sadhana; Ika Pawitra Miranti; Hermawan Istiadi (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : The upper respiratory tract is susceptible to inflammation caused by exposure to airborne contaminants, particularly chemical irritants. Inhaled irritant gases can lead to various symptoms and adverse reactions in the respiratory tract. Laboratory workers are at a high risk of respiratory tract inflammation due to exposure to volatile chemicals. The use of personal protective equipment (PPE), such as masks, is essential to prevent inflammation and protect the respiratory tract. Lung function tests using spirometry, including Forced Vital Capacity (FVC), Forced Expiratory Volume in One Second (FEV1.0), and Peak Expiratory Flow (PEF), can help identify abnormalities in lung function. AIMS :  The primary objective of this investigation is to juxtapose the pulmonary conditions of laboratory workers before and after the utilization of KN95® masks and Acchadana® masks. METHOD : The study design was a Randomized Control Trial, and the subjects were divided into two groups: the control group wearing KN95 masks and the treatment group wearing Acchadana® herbal masks. Spirometry measurements were taken before and after using the masks, and statistical analysis was conducted to compare the results. RESULT :  The results showed that both mask groups experienced improvements in lung function parameters after using the masks. However, the KN95 mask group showed better lung conditions compared to the Acchadana® mask group. CONCLUSION : Spirometry tests conducted on lab workers revealed improved lung function metrics (including FVC, FEV1.0, and PEF) following the usage of KN95 masks and Acchadana® herbal masks. The KN95 mask users exhibited superior respiratory health compared to the other group in this investigation.